2004
DOI: 10.1089/108729104322994838
|View full text |Cite
|
Sign up to set email alerts
|

Service Needs of Patients with Advanced HIV Disease: A Comparison of Client and Staff Reports at Three Palliative Care Projects

Abstract: Despite prolonged survival and improved quality of life as a result of treatment advances for HIV/AIDS, thousands still suffer with the disease and 15-16,000 a year die in the United States alone. Little is known about those patients with HIV/AIDS who still require palliative care services or the types of services needed. This paper describes the program elements and clients of three programs providing palliative care to persons with HIV/AIDS in Alabama (n = 41), Baltimore, Maryland, (n = 55), and New York Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Early diagnosis and initiation of ART based on current treatment guidelines could reduce HIV- related morbidity and mortality [ 16 ]. The majority of the participants had first CD4 count test results below 350 cells/mm 3 before their enrollment on ART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early diagnosis and initiation of ART based on current treatment guidelines could reduce HIV- related morbidity and mortality [ 16 ]. The majority of the participants had first CD4 count test results below 350 cells/mm 3 before their enrollment on ART.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, healthcare facilities that provide HIV/AIDS services do not facilitate provision of comprehensive support services such as HIV/AIDS case management, peer group support, medication adherence, and nutritional enhancement among others due to inadequate resources. Meanwhile other studies have demonstrated that the provision of support services such as health insurance and transportation services is associated with retention of care of HIV patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…HIV/AIDS patients with advanced disease continue to live with not only a risk of dying from the disease itself, but increasingly also from significant co-morbidities such as hepatitis and a variety of malignancies. Like their counterparts living with cancer, patients with advanced HIV/AIDS and their informal caregivers must continually cope with health care issues such as symptom management and threats posed by their illness to their psychological well being (28,29). Despite such similarities with regard to the caregiving situation, important sociodemographic differences between the HIV/AIDS and cancer patient populations associated with risk of infection with HIV, e.g., race/ethnicity, sexual orientation, history of intravenous drug use, age, suggest a need to further investigate patient-caregiver agreement within the context of HIV.…”
Section: Introductionmentioning
confidence: 99%
“…HIE interventions can play a crucial role in facilitating the sharing of information among providers across the continuum of HIV care, which in turn can help close each of these gaps [28][29][30][31][32]. For instance, in settings where patients do not engage or remain in HIV care, it is possible to use coordinated information technology systems to identify out-of-care patients when they utilize any type of care (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…medical case management) for those who have co-occurring conditions that impact the effectiveness of HIV care [26,27]. Previous research in RWP-funded health clinics suggests receipt of care and support services in RWP-funded health clinics are associated with better engagement in care, retention in care and patient health outcomes [28][29][30][31][32]. However, these same findings also indicate that the improved engagement, retention and health outcomes are not yet at levels that would be considered ideal [30].…”
Section: Introductionmentioning
confidence: 99%